Business Process Management Implementation to Increase Revenue PT. XYZ Using Balanced Scorecard Measurement Tool - Lorio Purnomo (Jurnal Manajemen Informatika (JAMIKA), 2022)
PT. XYZ has three subsidiaries, which run Digital Business, and the other one of another company that handles the field of human resource development. In running its business PT. XYZ gets the biggest revenue from PT. A. In 2011 there was a change in regulations from the Government of Indonesia at the Ministry of Communications. This change made it difficult for PT XYZ to achieve Annual Income, the decline in Revenue experienced made PT. XYZ must find a solution with several approaches. The researcher provides input with the BPM (Business Process Management) method approach, for PT. XYZ and all subsidiaries under it. The purpose of this research is to help PT XYZ formulate the best performance based on KPI (Key Performance Indicator) for all HR (Human Resources) in pursuing Revenue Targets, as well as reducing the cost of Human Resources. The Balanced Scorecard measurement method was chosen to determine the constraints in each unit of three subsidiaries of PT XYZ because there are so many employees working in the same field. The results of this paper, with the Balanced Score Card Method, create performance development in the three subsidiaries of PT XYZ and can find out the similarities in the KPIs in the work process in the IT division of the three subsidiaries under it. Functional changes in everyone who works at PT. XYZ is expected to be able to provide support to three subsidiaries of PT. XYZ. So that the Revenue Target in the following year can be achieved.